The Cabinet Radiology School of Medicine - Villarán, Manuel Vicente (1923)
On September 5 took place in the hospital, "Dos de Mayo" in Lima, the opening ceremony of the gifted to the Faculty of Medicine of Lima by the philanthropist D. Antero Aspíllaga Radiological Cabinet.